[Clinical practice guideline for the management of essential hypertension in the Peruvian Social Security (EsSalud)] - Sotomayor-Perales, Jorge Luis (2024)
Introduction: This article summarizes the clinical practice guide (CPG) for management of essential arterial hypertension in the Social Security of Peru (EsSalud). Objective: To provide evidence-based clinical recommendations for management of essential arterial hypertension in EsSalud. Methods: A guideline development group (GDG) was formed, which included specialist physicians and methodologists, who formulated clinical questions. Systematic searches of systematic reviews were conducted and - when deemed relevant - primary studies in PubMed during 2022. Evidence was selected to answer each of the proposed clinical questions. The certainty of evidence was assessed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. In periodic working meetings, the GDG used the GRADE methodology to review the evidence and formulate recommendations, points of good clinical practice, and flowcharts. Finally, the CPG was approved with Resolution No. 109-IETSI-ESSALUD-2022. Results: The CPG addressed 6 clinical questions regarding management. Based on these questions, 14 recommendations were formulated (7 strong and 7 conditional), 2 points of good clinical practice, and 1 flow chart. Conclusion: Evidence-based recommendations were statement for the management of patients with essential arterial hypertension.